An Expedient Synthesis of 2,4,6-Tris(trifluoromethyl)aniline - Edelbach, Brian L.; Pharoah, Blaze M.; Bellows, Sarina M.; Thayer, Peter R.; Fennie, Charles N.; Cowley, Ryan E.; Holland, Patrick L. (Synthesis, 2012)
A simple two-step synthetic route leads to 2,4,6-tris(trifluoromethyl)aniline. It proceeds through deprotonation and iodination of 1,3,5-tris(trifluoromethyl)benzene, followed by copper-catalyzed amination.
Keywords: fluorination; aniline; ligand precursor